Chromium isotope fractionation during Cr(VI) reduction in a methane-based hollow-fiber membrane biofilm reactor. (1st March 2018) - Lu, Yong-Ze; Chen, Guo-Jun; Bai, Ya-Nan; Fu, Liang; Qin, Li-Ping; Zeng, Raymond Jianxiong
Abstract: Chromium (Cr) isotope fractionation analysis is a promising tool for monitoring Cr(VI) reduction in natural aqueous systems. In addition, large amounts of CH4 in natural aqueous sediments are oxidized to CO2 through methanotrophs, thereby mitigating emissions to the atmosphere. However, the investigations on the Cr(VI) reduction process with methanotrophs, and the associated Cr isotope fractionation patterns are scarce. In this study, we have shown that Cr(VI) reduction can occur in the presence of CH4 as the sole electron donor in a hollow-fiber membrane reactor (HfMBR) after direct bacteria enrichment from sediment samples. Products of the methane oxidation by the methanotrophs are used by microbes to reduce Cr(VI) as shown by the progressive increase in δ 53 Cr with time in the CH4 feed reactor. The isotope fractionation factor ( ε ) of −2.62 ± 0.20‰ was obtained from the application of the Rayleigh distillation model. The results of Cr isotope fractionation analysis also explained the decrease of Cr(VI) concentration in the N2 feed reactor, where the δ 53 Cr values remained steady in the first two weeks but significantly increased in the last two weeks, indicating that physical adsorption and subsequent Cr(VI) reduction occurred. This study extended the application of Cr isotope fractionation, showing the suitability of this method for clarifying different Cr(VI) removal processes. Graphical abstract: Highlights: Microbial Cr(VI) reduction was occurred with products produced by methanotrophs. CH4 or N2 related Cr(VI) reduction was identified by Cr isotope fractionation. Cr isotope fractionation factor ( ε ) value was 2.62 ± 0.20‰ with CH4 oxidation. Adsorption and reduction of Cr(VI) were distinguished in N2 reactor by Cr isotope.